2017
DOI: 10.1159/000487139
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell Neurotrophin Production Is Associated with Subcortical Brain Atrophy in Neuropsychiatric Systemic Lupus Erythematosus Patients

Abstract: Objective: Central nervous system (CNS) involvement in systemic lupus erythematosus (SLE) remains poorly understood. Damage within the CNS is driven by the autoimmune response; however, immunopathophysiology of neuropsychiatric (NP) SLE is multifactorial. Immune cell neurotrophin production could be neuroprotective against autoimmunity-driven CNS damage, as has been shown in multiple sclerosis. The aim of this study was to establish whether immune cell neurotrophin production is associated with damage severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Another study suggests a contribution of the age-related decline of BDNF serum levels to hippocampal volume as well as memory decline in late adulthood (61). In patients with systemic lupus erythematosus with neuropsychiatric manifestation, immune cell NGF levels were found to be correlated with brain atrophy reflected by lateral ventricle enlargement and thalamic volume loss (62).…”
Section: Introductionmentioning
confidence: 99%
“…Another study suggests a contribution of the age-related decline of BDNF serum levels to hippocampal volume as well as memory decline in late adulthood (61). In patients with systemic lupus erythematosus with neuropsychiatric manifestation, immune cell NGF levels were found to be correlated with brain atrophy reflected by lateral ventricle enlargement and thalamic volume loss (62).…”
Section: Introductionmentioning
confidence: 99%
“…24 In contrast, BDNF within peripheral blood mononuclear cells showed a significant negative correlation with disease activity in NpSLE patients and protective role of the higher BDNF concentrations against disease activity were suggested. 25 In addition, studies had shown a negative correlation between SLEDAI scores and BDNF levels. 28,29 In our study, we did not observe a significant correlation between BDNF levels and SLEDAI score but BDNF levels were lower in patients with SLEDAI score ≥ 1.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] In contrast, some studies suggested that active SLE patients presented with higher BDNF levels as a compensatory mechanism. 25,26 Ikenouchi et al 27 reported that serum BDNF levels were increased in the presence of severe psychiatric symptoms due to the organic changes in the brain. On the contrary, low BDNF levels in the presence of neuropsychiatric SLE (NpSLE) might be explained by the impairment of neurons and endothelial cells that produce BDNF due to the endothelial and blood-brain barrier dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…According to Table 1, eight studies published from 2009 to 2021 provided original data on BDNF blood levels in SLE patients and HCs [26][27][28][29][30][31][32][33]. SLE patients were selected based on the ACR criteria.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…SLE patients were selected based on the ACR criteria. Two studies only compared BDNF levels in SLE patients (n = 59) to HCs (n = 64) [27,29]. Meanwhile, six studies gave All but one study [26] used enzyme-linked immunosorbent assay (ELISA) to measure BDNF levels as an analytical procedure.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%